A High-Throughput Screening Model of the Tumor Microenvironment for Ovarian Cancer Cell Growth. (June 2017) - Lal-Nag, Madhu; McGee, Lauren; Guha, Rajarshi; Lengyel, Ernst; Kenny, Hilary A.; Ferrer, Marc
The tumor microenvironment plays an important role in the processes of tumor growth, metastasis, and drug resistance. We have used a multilayered 3D primary cell culture model that reproduces the human ovarian cancer metastatic microenvironment to study the effect of the microenvironment on the pharmacological responses of different classes of drugs on cancer cell proliferation. A collection of oncology drugs was screened to identify compounds that inhibited the proliferation of ovarian cancer cells growing as monolayers or forming spheroids, on plastic and on a 3D microenvironment culture model of the omentum metastatic site, and also cells already in preformed spheroids. Target-based analysis of the pharmacological responses revealed that several classes of targets were more efficacious in cancer cells growing in the absence of the metastatic microenvironment, and other target classes were less efficacious in cancer cells in preformed spheres compared to forming spheroid cultures. These findings show that both the cellular context of the tumor microenvironment and cell adhesion mode have an essential role in cancer cell drug resistance. Therefore, it is important to perform screens for new drugs using model systems that more faithfully recapitulate the tissue composition at the site of tumor growth and metastasis.